Status and future of the Juelich CV28 compact cyclotron - Hölzle, R. (Вопросы атомной науки и техники, 2006)
The parameters of compact cyclotron with changeable energy CV28 and modernization of its systems and possible applications of the accelerated protons, deuterons, ³Не and alpha particles is described